Effect of curcumin nanoparticles on proliferation and migration of mouse airway smooth muscle cells and airway inflammatory infiltration - Ma, Yucong; Ye, Suping; Sun, Kunpeng; Gu, Yue (Frontiers in Pharmacology, 2024)
Curcumin (CUR) possesses the capability to inhibit various inflammatory factors, exert anti-inflammatory effects, and alleviate asthma attacks; however, its hydrophobicity and instability significantly impede its clinical application. In this study, we synthesized CUR-loaded nanoparticles (CUR-NPs) and evaluated their impact on the proliferation, migration, and inflammatory infiltration of mouse airway smooth muscle cells (ASMCs), while investigating their underlying mechanisms. To achieve this objective, ASMCs were isolated from BALB/c mice and subjected to TGF-1-induced cell proliferation and migration. Our findings demonstrate that CUR-NPs effectively regulate the release of CUR within cells with superior intracellular uptake compared to free CUR. The CCK-8 assay results indicate that the blank carrier does not exhibit any cytotoxic effects on cells, thus rendering the impact of the carrier itself negligible. The TGF-1 group exhibited a significant increase in cell proliferation, whereas treatment with CUR-NPs significantly suppressed TGF-1-induced cell proliferation. The findings from both the cell scratch assay and transwell assay demonstrated that TGF-1 substantially enhanced cell migration, while CUR-NPs treatment effectively attenuated TGF-1-induced cell migration. The western blot analysis demonstrated a substantial increase in the expression levels of TGF-1, p-STAT3, and CTGF in ASMCs following treatment with TGF-1 when compared to the control group. Nevertheless, this effect was effectively counteracted upon administration of CUR-NPs. Furthermore, an asthma mouse model was successfully established and CUR-NPs were administered through tail vein injection. The serum levels of TGF-1 and the expression levels of TGF-1, p-STAT3, and CTGF proteins in the lung tissue of mice in the model group exhibited significant increases compared to those in the control group. However, CUR-NPs treatment effectively attenuated this change. Our research findings suggest that CUR-NPs possess inhibitory effects on ASMC proliferation, migration, and inflammatory infiltration by suppressing activation of the TGF-1/p-STAT3/CTGF signaling pathway, thereby facilitating inhibition of airway remodeling.